2015
DOI: 10.1186/s13054-015-1149-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term remote organ consequences following acute kidney injury

Abstract: Acute kidney injury (AKI) has been a global health epidemic problem with soaring incidence, increased long-term risks for multiple comorbidities and mortality, as well as elevated medical costs. Despite the improvement of patient outcomes following the advancements in preventive and therapeutic strategies, the mortality rates among critically ill patients with AKI remain as high as 40–60 %. The distant organ injury, a direct consequence of deleterious systemic effects, following AKI is an important explanation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 124 publications
(170 reference statements)
2
39
0
Order By: Relevance
“…These patients may nonetheless be vulnerable to further kidney damage and other adverse events. As has been shown previously, patients who have suffered an AKI event and 'recover' still carry a long-term increased risk of major adverse cardiac and kidney events 49,76 . Patients with AKD stage 0A might still require follow-up and could likely benefit from avoiding unnecessary nephrotoxic drugs.…”
Section: A Framework To Classify Akd and Recoverymentioning
confidence: 82%
“…These patients may nonetheless be vulnerable to further kidney damage and other adverse events. As has been shown previously, patients who have suffered an AKI event and 'recover' still carry a long-term increased risk of major adverse cardiac and kidney events 49,76 . Patients with AKD stage 0A might still require follow-up and could likely benefit from avoiding unnecessary nephrotoxic drugs.…”
Section: A Framework To Classify Akd and Recoverymentioning
confidence: 82%
“…The largest proportion in our study could be explained by the delay in the management of our patients related to the precarious socio-economic conditions of these and the lack of social security system. Factors such as sepsis, hypertension and cancer seem associated with the non recovery of renal function during AKI (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] The conventional wisdom that AKI survivors with renal functional recovery tend to do well and be uneventful should be abandoned. [12][13][14] The severity, frequency and duration of AKI have been demonstrated to be associated with the ensuing incident CKD. 7,8,10 AKI and CKD have been seen as interconnected syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have identified that AKI is a major risk of ensuing chronic kidney disease (CKD) . The conventional wisdom that AKI survivors with renal functional recovery tend to do well and be uneventful should be abandoned . The severity, frequency and duration of AKI have been demonstrated to be associated with the ensuing incident CKD .…”
mentioning
confidence: 99%